Aggressiveness of End‐of‐Life Care for Hospitalized Individuals with Cancer with and without Dementia: A Nationwide Matched‐Cohort Study in France. Issue 9 (26th July 2016) - Morin, Lucas; Beaussant, Yvan; Aubry, Régis; Fastbom, Johan; Johnell, Kristina
Abstract : Objectives: To compare the aggressiveness of end‐of‐life care in hospitalized individuals with cancer with and without dementia in France. Design: Nationwide register‐based matched‐cohort study. Setting: Hospital facilities in France. Participants: All individuals with cancer aged 65 and older with a diagnosis of dementia who died between January 1, 2010 and December 31, 2013, matched one‐to‐one with individuals with cancer without dementia (n = 26, 782 matched pairs). Results: Older individuals with cancer with dementia were less likely to receive aggressive treatment in their last month of life than those who were not diagnosed with dementia. Dementia was associated with significantly greater likelihood of receiving chemotherapy (2.8% vs 8.5%, P < .001, adjusted odds ratio (aOR) = 0.33, 95% confidence interval (CI) = 0.31–0.36) in the month before death. Individuals with dementia were also less likely to receive radiation therapy (aOR = 0.49, 95% CI = 0.43–0.56), blood transfusions (aOR = 0.67, 95% CI = 0.64–0.70), artificial nutrition (aOR = 0.79, 95% CI = 0.73–0.85), and invasive ventilation (aOR = 0.62, 95% CI = 0.57–0.68), although they were more likely to remain hospitalized over their entire last month of life (aOR = 1.42, 95% CI = 1.37–1.48) and to have more than one emergency department visit (aOR = 1.22, 95% CI = 1.12–1.34). Conclusion: Older hospitalized adults with cancer with dementia are less likely to receive aggressive cancer treatment near the end of life than those without dementia. This discrepancy raises important ethical questions for clinicians and healthcare policy‐makers.